Ultra-sound assisted nano Y- zeolite /Mn adsorbent to removed sulfur from crude oil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are some types of crude oil that contains large quantities of various sulfur compounds that have great harm on the environment, oil economy, oil sector facilities such as fields and refineries.So developing ways to get rid of it is one of the most important goals of researchers in this sector. In this study, nanotechnology was used for environmentally friendly and available industrial materials (nano-zeolite Y), which can adsorb sulfur from crude oil, especially when it impregnated with manganese metals with ultrasound to increase the adsorption efficiency.  The effect (temperature, adsorbent dose, Samples PH) was studied with ultrasound and without ultrasound.On the efficiency of removal had best results with ultrasound andit was found that this material is highly efficient in removing sulfur compounds, especially at a temperature of 100 C, and at a dose of 13 g, and PH 7 it found the best adsorption efficiency about 99 %. The change in the properties of the adsorbent material is almost non-existent, with a change in the surface area and pore size.